Stock index adjustments, analyst coverage and institutional holdings: Evidence from China - Song Zhu; Xiaoyu Jiang; Xiaoli Ke; Xiaoyu Bai (China Journal of Accounting Research, 2017)
Using 231 pairs of matched firms from 2009 to 2012 in Chinese stock market, we find that the stock index adjustment significantly affects the analyst coverage, which in addition to the stock index leads to more analyst coverage, while deletion from the stock index has no significant effect, indicating that stock index adjustment can significantly change the information environments of firms that are added to the index. An index adjustment also affects institutional holdings in consideration of new information (e.g., changes in fundamentals and information environments). Changes in institutional holdings are partially due to changes in analyst coverage, and both index funds and other types can change their portfolios in response to changes in the target firms' informativeness.
Keywords: G2; M3; 650; Stock index adjustment; Analyst coverage; Institutional holding